Práticas on-off no mercado de arte: visibilidade e inovação - Silveira, Andrea Aparecida Capssa de Lima da (2023)
This doctoral research in Visual Arts conceptualizes and defends the nomenclature of ON-OFF Practices in the field of Contemporary Art, as a classifier of galleries that seek to achieve greater visibility from the dynamism of networks, online environments and partnerships with agents active in the art market. By developing Moblanc Gallery and selecting ON-OFF Practices, in face of its participations in art fairs and by means of gallery collectives with online actions, we propose the analysis and discussion of its dynamics of insertion in the market. This theoretical and practical study, based on specific research methodologies in History, Theory and Art Criticism, of qualitative approach, emphasis on art and technology, starts from the bibliographic review with emphasis on Lipovetsky and Serroy that point out the production in art directly linked to market interests. It aims to understand how technology and digital strategies can help the agents of the art market to act remotely. As a contribution to the art system, with the development of the Mobart platform, the research also assesses whether innovative platforms such as this one meet contemporary demands, including in the post-pandemic, and which agents are involved in the operations, since this thesis is developed during the covid-19 pandemic.